Modeling and composing navigational concerns in web applications : Requirements and design issues - Gordillo, Silvia Ethel (^p Datos electrónicos (1 archivo : 295 KB))
Complex applications, in particular Web applications, deal with a myriad of different concerns and some of them affect several others. The result is that these crosscutting concerns are scattered throughout different software artifacts and tangled with other concerns. In this paper we present an approach for modeling and composing navigational concerns in Web applications. By showing how to build partial navigation scenarios with user interaction diagrams, analyzing how they crosscut and defining corresponding composition rules, we add modularity to the requirements specification stage, facilitating reasoning about the requirements and a consequent tradeoff analysis to support informed decisions of on architectural choices Moreover, by focusing on navigation concerns during the early stages of applications development, we aim to address the impact of crosscutting concerns in design models, improve the discovering of meaningful design artefacts and improve traceability of design decisions.